Zoonotic Diseases and One Health - Fontanilla, Ian Kendrich (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Humans are part of an ecosystem, and understanding our relationship with the environment and with other organisms is a prerequisite to living together sustainably. Zoonotic diseases, which are spread between animals and humans, are an important issue as they reflect our relationship with other animals in a common environment. Zoonoses are still presented with high occurrence rates, especially in rural communities, with direct and indirect consequences for people. In several cases, zoonosis could cause severe clinical manifestations and is difficult to control and treat. Moreover, the persistent use of drugs for infection control enhances the potential of drug resistance and impacts on ecosystem balance and food production. This book demonstrates the importance of understanding zoonosis in terms of how it allows ecosystems to transform, adapt, and evolve. Ecohealth/One Health approaches recognize the interconnections among people, other organisms, and their shared developing environment. Moreover, these holistic approaches encourage stakeholders of various disciplines to collaborate in order to solve problems related to zoonosis. The reality of climate change necessitates considering new variables in studying diseases, particularly to predict how these changes in the ecosystems can affect human health and how to recognize the boundaries between medicine, veterinary care, and environmental and social changes towards healthy and sustainable development.